Inflammatory pseudotumor involving sternoclavicular articulation - Costa, Teresa Catarina (2009)
Inflammatory pseudotumor is a rare condition with unknown etiology that most commonly involves the lung and the orbit, but it has been reported to occur in nearly every site in the body. Because inflammatory pseudotumors mimic malignant tumours, both clinically and radiologically, they represent a diagnostic dilemma.We report the case of a patient with inflammatory pseudotumor involving the left sternoclavicular articulation.